Preparation method and application of chromium nitride-copper nitride composite film

The magnetron sputtering process alternately reacts the copper nitride and chromium nitride layers to prepare a chromium nitride-copper nitride composite film, and a solid-liquid composite lubrication system is constructed with polyα-olefin (PAO), which solves the problem of abnormally increasing wear rate and film peeling in a single chromium nitride film in the solid-liquid composite lubrication system, and achieves excellent friction coefficient and wear rate performance.

CN119553239APending Publication Date: 2025-03-04YANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411858235.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The wear rate of a single structure chromium nitride film in the solid-liquid composite lubricating system is abnormally increased, and adhesion wear is prone to occur to cause film peeling.

Method used

The copper nitride and chromium nitride layer were alternately reacted to sputter the copper nitride and chromium nitride layers by magnetron sputtering process to prepare a chromium nitride-copper nitride composite film, and a solid-liquid composite lubricating system was constructed with polyα-olefins (PAO).

Benefits of technology

The problem of abnormally increasing wear rate and film peeling in a solid-liquid composite lubricating system was solved. The friction coefficient and wear rate of the CrN/Cu3N composite film were better than that of a single chromium nitride or a single copper nitride film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553239A_ABST
    Figure CN119553239A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a chromium nitride-copper nitride composite film, and the preparation method comprises the following steps: sputtering a chromium target material with the purity of 99.9% by magnetron sputtering to obtain a pure chromium transition layer; a copper target material with the purity of 99.9% is subjected to reactive sputtering on the pure chromium transition layer, and a copper nitride layer is obtained; performing reactive sputtering on a chromium target material with the purity of 99.9% to obtain a chromium nitride layer; and alternately sputtering a copper nitride layer and a chromium nitride layer to prepare the chromium nitride-copper nitride composite film. The problems that the wear rate of a single chromium nitride thin film in a solid-liquid composite lubricating system is increased abnormally, and the thin film is stripped due to adhesive wear are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thin film materials, and in particular relates to a preparation method of a chromium nitride-copper nitride composite thin film and application thereof. Background Art

[0002] In recent years, hard films such as TiN, CrN, and DLC (diamond-like carbon) have attracted widespread attention due to their high hardness and wear resistance. As a typical example of hard films, binary nitride films, such as CrN, have high hardness, excellent wear resistance, and chemical stability, and are widely used in cutting tools, molds, and other fields.

[0003] However, with the continuous improvement of modern machining efficiency and precision, thin films with a single structure are unable to meet the requirements of comprehensive mechanical properties. Multilayer films are made by stacking two or more components with different properties. Compared with single-layer films, multilayer films have rich heterogeneous interfaces that can inhibit the formation of coarse columnar crystals, greatly enhancing the ductility of the film and inhibiting crack propagation.

[0004] Therefore, it is of great significance to design a multilayer CrN / Cu3N composite film and achieve low friction at the interface by constructing a solid-liquid composite lubrication system. Summary of the Invention

[0005] The purpose of this section is to summarize some aspects of the embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the abstract and title of this application to avoid obscuring the purpose of this section, the abstract and the title of the invention, and such simplifications or omissions should not be used to limit the scope of the present invention.

[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0007] Therefore, the object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a chromium nitride-copper nitride composite film.

[0008] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing a chromium nitride-copper nitride composite film, comprising: A pure chromium transition layer is obtained by sputtering a chromium target with a purity of 99.9% using magnetron sputtering; A copper target with a purity of 99.9% is reactively sputtered on the pure chromium transition layer to obtain a copper nitride layer; Reactive sputtering of a 99.9% pure chromium target to obtain a chromium nitride layer; Copper nitride layers and chromium nitride layers are alternately sputtered to prepare a chromium nitride-copper nitride composite film.

[0009] As a preferred embodiment of the preparation method of the present invention, the thickness of the pure chromium layer is 300-400 nm.

[0010] As a preferred embodiment of the preparation method of the present invention, the sputtering parameters for obtaining the pure chromium transition layer are: The DC sputtering pressure is 0.5~1.5Pa, the temperature is 130~180℃, the argon flow rate is 50~80sccm, and the sputtering power is 80~130W.

[0011] As a preferred embodiment of the preparation method of the present invention, the sputtering parameters for obtaining the copper nitride layer are: The reactive sputtering pressure is 0.5~1.5Pa, the temperature is 130~180℃, the argon flow rate is 50~80sccm, the nitrogen flow rate is 5~20sccm, the sputtering power is 200~300W, and the bias voltage is -50~-100V.

[0012] As a preferred embodiment of the preparation method of the present invention, the thickness of the copper nitride layer is 550-600 nm.

[0013] As a preferred embodiment of the preparation method of the present invention, the sputtering parameters for obtaining the chromium nitride layer are: The reactive sputtering pressure is 0.5~1.5Pa, the temperature is 130~180℃, the argon flow rate is 50~80sccm, the nitrogen flow rate is 5~20sccm, the sputtering power is 200~300W, and the bias voltage is -50~-100V.

[0014] As a preferred embodiment of the preparation method of the present invention, the thickness of the chromium nitride layer is 400-450 nm.

[0015] As a preferred solution of the preparation method of the present invention, the thickness of the composite film is 5-6 μm, and the top layer of the composite film is a copper nitride layer.

[0016] Another object of the present invention is to overcome the deficiencies in the prior art and provide a chromium nitride-copper nitride composite film prepared by a preparation method.

[0017] Another object of the present invention is to overcome the deficiencies in the prior art and provide a chromium nitride-copper nitride composite film for use as a friction-reducing and anti-wear coating under PAO lubrication conditions.

[0018] (1) The present invention solves the problem of abnormal increase in wear rate of a single chromium nitride film in a solid-liquid composite lubrication system and the occurrence of adhesive wear leading to film peeling.

[0019] (2) The present invention uses a magnetron sputtering process to alternately sputter chromium nitride and copper nitride films onto the substrate surface. The target product CrN / Cu3N composite film is used as a friction-reducing and anti-wear film to construct a solid-liquid composite lubrication system with polyα-olefin (PAO), solving the problem of film peeling caused by adhesive wear.

[0020] (3) The CrN / Cu3N composite film in the present invention is more effective than single chromium nitride or single copper nitride, and CrN and Cu3N have a synergistic lubricating effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. Those skilled in the art can also derive other drawings based on these drawings without inventive effort. Among them: Figure 1 These are the physical images and electron microscope scanning images in the embodiments of the present invention; wherein, I is the physical image of lubricating oil PAO10, II is the image of the stainless steel 304 substrate, III is the product image of Example 1, IV is the product image of Example 2, V is the product image of Example 3, VI is the product image of Example 4, VII is the scanning electron microscope cross-sectional image of Example 1, VIII is the scanning electron microscope cross-sectional image of Example 2, IX is the scanning electron microscope cross-sectional image of Example 3, and X is the scanning electron microscope cross-sectional image of Example 4.

[0022] Figure 2 2 is a comparison chart of the nanomechanical performance data of Examples 1, 2, and 3 of the present invention.

[0023] Figure 3 The friction coefficient curves of the films prepared in Examples 1, 2, and 3 of the present invention at 25° C., a load of 6 N, a frequency of 4 Hz, an amplitude of 5 mm, and a long grinding time of 60 min are shown.

[0024] Figure 4 Graph showing the wear rate of the wear scar of the films prepared in Examples 1, 2, and 3 of the present invention at 25° C., a load of 6 N, a frequency of 4 Hz, an amplitude of 5 mm, and a long wear time of 60 min.

[0025] Figure 5 The friction coefficient curves of the films prepared in Examples 1, 2, 3, and 4 of the present invention at 25° C., a load of 6 N, a frequency of 4 Hz, an amplitude of 5 mm, and a long grinding time of 120 min are shown.

[0026] Figure 6 Graph showing the wear rate of the wear scar of the films prepared in Examples 1, 2, 3, and 4 of the present invention at 25° C., a load of 6 N, a frequency of 4 Hz, an amplitude of 5 mm, and a long wear time of 120 min. DETAILED DESCRIPTION

[0027] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0028] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0029] Secondly, the term "one embodiment" or "embodiment" herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in various places throughout this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive of other embodiments. Example

[0030] (1) First, a chromium target with a purity of 99.9% was DC sputtered on the cleaned 304 stainless steel substrate at a pressure of 0.5 Pa, a temperature of 130 °C, an argon flow rate of 50 sccm, and a sputtering power of 100 W. After sputtering for 30 min, a transition layer of CrN / Cu3N composite film was obtained. (2) Then, with the above-obtained transition layer as the substrate, a copper target with a purity of 99.9% was reactively sputtered, and the sputtering pressure was controlled to be 0.5 Pa, the temperature was 130 ° C, the argon flow rate was 50 sccm, the nitrogen flow rate was 15 sccm, the sputtering power was 200 W, the bias voltage was -100 V, and the time was 20 min to obtain a copper nitride layer of the CrN / Cu3N composite film with a thickness of about 600 nm; (3) On the basis of the above coating, the chromium target was reactively sputtered, and the sputtering pressure was controlled to be 0.5 Pa, the temperature was 100 ° C, the argon flow rate was 50 sccm, the nitrogen flow rate was 15 sccm, the sputtering power was 200 W, the bias voltage was -100 V, and after 20 minutes, the chromium nitride layer of the composite film was obtained, with a thickness of about 450 nm.

[0031] (4) According to the above-mentioned parameters for plating copper nitride layer and chromium nitride layer, the copper target and the chromium target are sputtered alternately for 3 hours, and finally a CrN / Cu3N composite film with a surface capped with a copper nitride layer and a thickness of about 5 μm is obtained. Example

[0032] (1) Using the cleaned 304 stainless steel as the substrate, a chromium target with a purity of 99.9% was sputtered. The DC sputtering pressure was 0.5 Pa, the temperature was 130 °C, the argon flow rate was 50 sccm, the sputtering power was 100 W, and the sputtering time was 30 min.

[0033] (2) The chromium target with a purity of 99.9% was continuously subjected to reactive sputtering at a pressure of 0.5 Pa, a temperature of 130°C, an argon flow rate of 50 sccm, a nitrogen flow rate of 15 sccm, a sputtering power of 200 W, a bias voltage of -100 V, and a reactive sputtering time of 6 h, to obtain a chromium nitride film with a thickness of about 5 μm. Example

[0034] (1) Using the cleaned 304 stainless steel as the substrate, a chromium target with a purity of 99.9% was sputtered. The DC sputtering pressure was 0.5 Pa, the temperature was 130 °C, the argon flow rate was 50 sccm, the sputtering power was 100 W, and the sputtering time was 30 min.

[0035] (2) A copper target material with a purity of 99.9% was reactively sputtered at a pressure of 0.5 Pa, a temperature of 100°C, an argon flow rate of 50 sccm, a nitrogen flow rate of 15 sccm, a sputtering power of 200 W, a bias voltage of -100 V, and a reactive sputtering time of 3 h to obtain a copper nitride film with a thickness of about 5 μm. Example

[0036] (1) Using the cleaned 304 stainless steel as the substrate, a chromium target with a purity of 99.9% was sputtered. The DC sputtering pressure was 0.5 Pa, the temperature was 130 °C, the argon flow rate was 50 sccm, the sputtering power was 100 W, and the sputtering time was 30 min.

[0037] (2) A copper target with a purity of 99.9% and a chromium target with a purity of 99.9% were reactively sputtered simultaneously. The reactive sputtering pressure was 0.5 Pa, the temperature was 100 °C, the argon flow rate was 50 sccm, the nitrogen flow rate was 15 sccm, the sputtering power was 200 W, the bias voltage was -100 V, and the reactive sputtering time was 3 h. A CrN@Cu3N mixed film with a thickness of about 10 μm was obtained.

[0038] The physical pictures and electron microscope scanning pictures in the embodiment of the present invention are shown in Figure 1 ; Wherein, I is a physical image of lubricating oil PAO10, II is a image of a stainless steel 304 substrate, III is a image of the product of Example 1, IV is a image of the product of Example 2, V is a image of the product of Example 3, VI is a image of the product of Example 4, VII is a scanning electron microscope cross-sectional image of Example 1, VIII is a scanning electron microscope cross-sectional image of Example 2, IX is a scanning electron microscope cross-sectional image of Example 3, and X is a scanning electron microscope cross-sectional image of Example 4.

[0039] Evaluation of basic material properties: The hardness (H) and elastic modulus (E*) of the film were tested using a nanoindenter (Bruker, Hysitron T1990). The maximum load of the indenter was set to 6 mN, and the indentation depth did not exceed 10% of the total thickness of the film to avoid the influence of the substrate material on the intrinsic mechanical properties of the film. Five test points were randomly selected in the test area and the average value was taken to reduce the experimental error.

[0040] Depend on Figure 2 It can be seen that the nanohardness and elastic modulus values ​​of the chromium nitride film are greater than those of the composite film and greater than those of the copper nitride film, which is consistent with the actual situation.

[0041] Evaluation of tribological properties of products: 1. Friction coefficient measured using a TriboStudio friction and wear tester at 25°C, 4 Hz frequency, 5 mm amplitude, and 6 N load for 60 min. The test ball used was GCr15 bearing steel with a diameter of 5 mm and PAO10 as the lubricant. The lower sample is the CrN / Cu3N composite film prepared in Example 1; For comparison, the friction coefficients of Example 2 and Example 3 were also obtained under the same conditions; Depend on Figure 3 It can be seen that at 25 °C, both CrN / Cu3N composite film and Cu3N film can significantly reduce the friction coefficient, but the friction reduction performance of CrN / Cu3N composite film is better than that of Cu3N film and CrN film.

[0042] 2. The film prepared in Example 1 was tested using a 3D optical profilometer (Bruker, ContourGT) to measure the wear volume of the wear scar when the film was worn for 60 min at a temperature of 25°C, a frequency of 4 Hz, an amplitude of 5 mm, and a load of 6 N. The steel ball used in the test was GCr15 bearing steel with an F = 5 mm. For comparison, the wear scars of Examples 2 and 3 were also obtained under the same conditions; Depend on Figure 4 It can be seen that at 25 °C, both CrN / Cu3N composite film and Cu3N film can significantly reduce the wear amount, but the wear rate of CrN / Cu3N composite film is lower than that of Cu3N film and CrN film.

[0043] 3. Friction coefficient measured using a TriboStudio friction and wear tester at 25°C, 4 Hz frequency, 5 mm amplitude, and 6 N load for 120 min. The test ball used was GCr15 bearing steel with a diameter of 5 mm and PAO10 lubricant. The lower sample is the CrN / Cu3N composite film prepared in Example 1; For comparison, the friction coefficients of Examples 2, 3, and 4 were also obtained under the same conditions; Depend on Figure 5 It can be seen that at 25°C, both the CrN / Cu3N composite film and the Cu3N film can significantly reduce the friction coefficient, but the friction reduction performance of the CrN / Cu3N composite film is better than that of the Cu3N film and the CrN film. In addition, the wear reduction performance of the CrN@Cu3N mixed film without the alternating sputtering process is significantly weaker than that of the CrN film.

[0044] 4. The film prepared in Example 1 was tested using a 3D optical profilometer (Bruker, ContourGT) to measure the wear volume of the wear scar when abraded for 120 min at a temperature of 25°C, a frequency of 4 Hz, an amplitude of 5 mm, and a load of 6 N. The steel ball used in the test was GCr15 bearing steel with an F = 5 mm. For comparison, the wear scars of Examples 2, 3, and 4 were also obtained under the same conditions; Depend on Figure 6 It can be clearly seen that at 25°C, both the CrN / Cu3N composite film and the Cu3N film can significantly reduce the wear amount, but the wear rate of the CrN / Cu3N composite film is lower than that of the Cu3N film and the CrN film. In addition, the wear rate of the CrN@Cu3N mixed film without the alternating sputtering process is higher than that of the CrN film.

[0045] When the inventors conducted oil-lubricated friction experiments on magnetron sputtered chromium nitride films, they unexpectedly discovered that the wear rate of the film increased abnormally after using a lubricant. In addition, there is very little research on copper nitride materials in terms of friction and lubrication. The present invention uses the magnetron sputtering process to prepare CrN / Cu3N composite films for the first time. The composite of CrN and Cu3N synergistically reduces the friction coefficient of the oil-lubricated friction system.

[0046] Depend on Figure 3 and Figure 4 It can be seen that the effect of CrN / Cu3N composite film is better than that of single chromium nitride or single copper nitride; Figure 5 、 Figure 6 The addition of a mixed-plated film, CrN@Cu3N, also revealed that the CrN / Cu3N composite film performed better. The mixed-plated CrN@Cu3N film exhibited poor mechanical properties, high internal stress, and was prone to brittle fracture during friction. However, the CrN / Cu3N composite film overcame the mechanical deficiencies of the mixed-plated film and exhibited superior tribological performance to either single chromium nitride or single copper nitride, demonstrating the synergistic lubrication effect of CrN, Cu3N, and the lubricant.

[0047] Based on the current experimental data, the following related lubrication mechanism is obtained: the copper nitride sputtering time of the surface layer of the CrN / Cu3N composite film is short and the structure is dense. During the friction process, the copper nitride reacts with the lubricating oil to form a lubricating film, which prevents direct contact between the steel ball and the coating surface and plays a friction-reducing role. The chromium nitride layer has a higher hardness after the copper nitride layer on the surface is worn through, which plays an anti-wear role.

[0048] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, and all of these should be included in the scope of the present invention.

Claims

1. A method for preparing a chromium nitride-copper nitride composite film, characterized in that: include, A pure chromium transition layer is obtained by sputtering a chromium target material with a purity of 99.9% using magnetron sputtering; A copper target with a purity of 99.9% is reactively sputtered on the pure chromium transition layer to obtain a copper nitride layer; Reactive sputtering of a chromium target with a purity of 99.9% is performed to obtain a chromium nitride layer; The copper nitride layer and the chromium nitride layer are sputtered alternately to obtain a chromium nitride-copper nitride composite film.

2. The preparation method according to claim 1, characterized in that: The thickness of the pure chromium layer is 300-400 nm.

3. The preparation method according to claim 1 or 2, characterized in that: The sputtering parameters for obtaining the pure chromium transition layer are: The DC sputtering pressure is 0.5~1.5Pa, the temperature is 130~180℃, the argon flow rate is 50~80sccm, and the sputtering power is 80~130W.

4. The preparation method according to claim 1, characterized in that: The sputtering parameters for obtaining the copper nitride layer are: The reactive sputtering pressure is 0.5~1.5Pa, the temperature is 130~180℃, the argon flow rate is 50~80sccm, the nitrogen flow rate is 5~20sccm, the sputtering power is 200~300W, and the bias voltage is -50~-100V.

5. The preparation method according to claim 4, characterized in that: The thickness of the copper nitride layer is 550-600 nm.

6. The preparation method according to claim 1, characterized in that: The sputtering parameters for obtaining the chromium nitride layer are: The reactive sputtering pressure is 0.5~1.5Pa, the temperature is 130~180℃, the argon flow rate is 50~80sccm, the nitrogen flow rate is 5~20sccm, the sputtering power is 200~300W, and the bias voltage is -50~-100V.

7. The preparation method according to claim 6, characterized in that: The thickness of the chromium nitride layer is 400-450 nm.

8. The preparation method according to claim 1, characterized in that: The thickness of the composite film is 5-6 μm, and the top layer of the composite film is a copper nitride layer.

9. The chromium nitride-copper nitride composite film obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the chromium nitride-copper nitride composite film according to claim 9 as a friction reducing and anti-wear coating under PAO lubrication conditions.